What determines dairy household food waste? A case study from the costa rican dairy industry - Montero Vega, Mercedes (2023)
Household waste represents a big contributor to food waste, especially in higher-income countries. To understand consumer behavior, and therefore food waste, this study addresses food buying and storaging routines, sociodemographic characteristics and intrinsic product characteristics. Food waste has usually been studied in high[1]income countries, especially in Europe and North America. However, this research includes 343 direct interviews with Costa Rican consumers. We constructed a structural equation model using the Theory of planned behavior to understand dairy food waste. Results indicate that the least important determinants of food waste are sociodemographic characteristics, nonetheless, income correlates positively higher waste rates, as expected. Intrinsic characteristics of dairy products were an important determinant of waste; as consumers place more importance on these characteristics, less waste is produced. This is the first study in which food waste includes all of these constructs and that is settled in a developing country. Based on our results and the determinants of food waste, we discuss the political and research implications for household food waste reduction.